2007
DOI: 10.1002/ajmg.a.31853
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia‐telangiectasia: Mild neurological presentation despite null ATM mutation and severe cellular phenotype

Abstract: Ataxia-telangiectasia (A-T) is an autosomal recessive disorder characterized by progressive neurodegeneration, immunodeficiency, susceptibility to cancer, genomic instability, and sensitivity to ionizing radiation. A-T is caused by mutations that eliminate or inactivate the nuclear protein kinase ATM, the chief activator of the cellular response to double strand breaks (DSBs) in the DNA. Mild A-T is usually caused by ATM mutations that leave residual amounts of active ATM. We studied two siblings with mild A-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 54 publications
1
41
0
3
Order By: Relevance
“…Moreover, the cellular phenotype of these patients was indistinguishable from that of classical A-T: all the tested parameters of the DNA DSBs response were severely defective, as in typical A-T. This analysis showed that the severity of the neurological component of A-T was determined not only by ATM mutations but also by other influences yet to be found (Alterman et al, 2007). Researchers therefore started to search for mechanisms other then DNA DSBs to improve understanding of A-T neurodegeneration.…”
Section: Research Articlementioning
confidence: 68%
“…Moreover, the cellular phenotype of these patients was indistinguishable from that of classical A-T: all the tested parameters of the DNA DSBs response were severely defective, as in typical A-T. This analysis showed that the severity of the neurological component of A-T was determined not only by ATM mutations but also by other influences yet to be found (Alterman et al, 2007). Researchers therefore started to search for mechanisms other then DNA DSBs to improve understanding of A-T neurodegeneration.…”
Section: Research Articlementioning
confidence: 68%
“…The existence of genes that modify ATM loss-offunction phenotypes is hinted at by the fact that some A-T patients have little or no ATM protein yet have mild neurological presentation (Hassin-Baer et al 1999;Lavin et al 2006;Alterman et al 2007). Also, cell fusion studies showed that ATM −/− cells derived from different A-T patients fall into four distinct genetic complementation groups, suggesting that A-T phenotypes are caused by at least four different mutant genes (Murnane and Painter 1982;Buchwald 1995).…”
Section: Identification Of Genetic Modifiers Of Neurodegeneration In mentioning
confidence: 99%
“…A majority of mutations are truncating mutations with loss of ATM expression, and the remainder are missense mutations that lead to absent or reduced expression or to lost or reduced function of ATM protein that may be expressed at normal levels. A recent report of an ATM-null mutant with only mild neurologic manifestations points to a remarkable infl uence of other modifying factors in this disease [ 40 ]. The molecular pathogenesis of AT as well as the other recessive ataxias that share the same phenotype (ataxia telangiectasia-like disorder, AOA1, AOA2, and the recently proposed AOA3) [ 5 ], all seem related to defective DNA repair that is physiologically initiated after single-strand or double-strand breaks.…”
Section: New Facets Of Known Genesmentioning
confidence: 98%